Information seeking behaviour (ISB) and information needs satisfaction among postgraduate students in Universiti Teknologi Mara, Malaysia / Nur Hidayah Che Ahmat and Wan Nor Bayah Wan Kamarudin - Che Ahmat, Nur Hidayah; Wan Kamarudin, Wan Nor Bayah (2014)
This paper fills the gap in understanding the Information Seeking Behaviour (ISB) among the postgraduate students in Faculty of Hotel and Tourism Management, UiTM, Shah Alam, Malaysia. Specifically, the aims of this paper are to determine the information needs, to identify the main information source in ISB, and to investigate the relationship between ISB and information needs satisfaction. By using self-administered questionnaire adapted from previous researchers, some of the issues of interest were obtained. Result revealed that ISB of postgraduate students were motivated by a wide variety of information needs including the need to fulfil research requirements. Also, internet was found as the main formal source while conversation with friends/colleagues was the main informal source used in seeking and obtaining information needed. It is worth mentioning that ISB was positively correlated with information needs satisfaction. This study could be considered as a starting point for further studies and for comparisons across faculties and disciplines in the University particularly in social sciences disciplines pertaining to ISB of the postgraduate students.